Reducing hospital acquired infections and professional exposures to blood borne infections through training, surveillance and intervention - Le, Thi Anh Thu (International Journal of Infection Control, 2007)
Implementation of infection control measures, including training, surveillance and intervention, at Cho Ray Hospital has been successful in reducing the number of hospital acquired infections and professional exposures to blood borne infections, despite severe overcrowding and a growing number of HIV admissions at the hospital.